Robust nonparametric analysis of dynamic profits, prices and productivity: An application to French meat-processing firms. (28th December 2022) - Ang, Frederic; Kerstens, Pieter Jan
Abstract: Appropriately considering adjustment costs, this paper develops a robust nonparametric framework to analyse profits, prices and productivity in a dynamic context. Dynamic profit change is decomposed into a dynamic Bennet price indicator and a dynamic Bennet quantity indicator. The latter is decomposed into explanatory factors. It is shown to be a superlative indicator for the dynamic Luenberger indicator. The application focuses on 1, 638 observations of French meat-processing firms for the years 2012–2019. Using m -out-of- n bootstrapped data envelopment analysis, we obtain robust estimates and confidence intervals. The components of dynamic productivity growth fluctuate substantially. However, these fluctuations are often statistically insignificant.